The behaviour of consumer society in consuming food at restaurants and cafes / Sri Astuti and Himasari Hanan - Astuti, Sri; Hanan, Himasari (Faculty of Architechture , Planning & Surveying, 2011)
Commodity consumption behaviour in eating places is heavily influenced by design factors, either its atmosphere or serving facilities. The preferences of eating places are influenced by the social class of people. The study aims to gain insight on people’s behaviour at restaurants and cafes associated with the design of the eating places. Based on the observations made on three eating places, there are different eating place preference behaviours. Besides its design and facilities, however, there are two types of eating places, which are used either to consume the food served or to enjoy the atmosphere of the place.